2001
DOI: 10.1053/seiz.2000.0473
|View full text |Cite
|
Sign up to set email alerts
|

Acute intermittent porphyria, seizures, and antiepileptic drugs: a report on a 3-year-old Nigerian boy

Abstract: A 3-year-old Nigerian boy was treated with phenobarbitone after having a nonfebrile seizure. Two weeks later his urine was found to contain porphobilinogen, indicating that latent acute intermittent porphyria had been unmasked by phenobarbitone. The drug was discontinued and carbamazepine was substituted. The urine became free of porphobilinogen and the patient remained well. In developing countries phenobarbitone is the most widely used anticonvulsant; it must be avoided in acute intermittent porphyria, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Almost 90% of patients who inherit this disorder remain asymptomatic for lifetime [5]. This could be explained by the fact that the gene responsible for AIP has an incomplete penetrance so that the disease often exists in a latent form (i.e., without clinical or biochemical manifestations) and family history may not be imminent [6].…”
Section: Discussionmentioning
confidence: 99%
“…Almost 90% of patients who inherit this disorder remain asymptomatic for lifetime [5]. This could be explained by the fact that the gene responsible for AIP has an incomplete penetrance so that the disease often exists in a latent form (i.e., without clinical or biochemical manifestations) and family history may not be imminent [6].…”
Section: Discussionmentioning
confidence: 99%
“…44 In addition, predictive experimental systems, especially cultures of chick embryo liver cells, have proved very sensitive but often do not reflect clinical situations. 44,46,47 Some like the antifungal agent griseofulvin may be active porphyrogens in experimental systems or when taken orally but this may not be relevant when prescribed for external dermatological use, although best avoided. Well established websites and publications have now evolved from clinical practice over the last few decades to provide advice to clinicians concerning those drugs that are contra-indicated for patients with suspected underlying predisposition to acute porphyric attacks (see Table 2 legend for examples).…”
Section: Triggering Agents For Porphyriasmentioning
confidence: 99%
“…3 AIP has been reported in a young boy in a similar setting to ours, which had also been precipitated by phenobarbitone. 4 In developing countries, phenobarbitone is widely prescribed Although an increased contact between human and the (grey) squirrel was reported in Britain, Wyatt 1 concluded that no complications are to be expected after a squirrel bite and that no prophylactic antibiotics seem to be necessary. In the USA, squirrels have been implicated in the carriage and transmission of certain diseases, notably rickettsial disease and tularemia.…”
Section: Referencesmentioning
confidence: 99%
“…2,3 Two cases of severe disease were described from Nigeria, where a pyrexial illness associated with skin manifestations developed four to five days after a ground squirrel bite. 4 In Ghana, the ground squirrels are hunted for their meat and people seem to be aware of the serious risks of a bite. In the last three years, five patients presented at our district hospital with severe illness, which developed after a squirrel bite.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation